Gender integration and elementary‐age students' classroom belongingness: The importance of other‐gender peers. Issue 8 (28th March 2022) - Martin, Carol Lynn; Xiao, Sonya Xinyue; DeLay, Dawn; Hanish, Laura D.; Fabes, Richard A.; Morris, Stacy; Oswalt, Krista
Abstract: Most US students attend coeducational classes, but to what extent do students feel integrated into the entire classroom of their peers, especially with other‐gender (OG) peers? The major goal of this study was to investigate how variations in gender integration (GI), measured by students' expectancies about inclusion, efficacy, and social costs of interacting with OG peers, predicted school liking and classroom supportiveness over an academic year, using a short‐term longitudinal design. We also explored how students' expectancies changed over the year. Participants included elementary school students (515 school‐age children; 51% boys, M age = 9.08 years, SD  = 1.00; 3–5th grade; 26 classrooms). A two‐wave latent change score model showed that changes over the year varied depending on the type of expectancy, grade, and gender, with decreases in inclusion and efficacy for boys. Longitudinal path analyses conducted to assess whether GI expectancies predicted school belongingness showed that students' levels of OG inclusion in the Fall uniquely predicted changes in levels of school liking and classroom community over the year, even with many controls in the model. The findings demonstrate that students' relationships with OG peers matter for having a sense of belonging in school, and educators should support and encourage these relationships. Keypoints: Gender integration (GI) within classrooms involves students forming positive relationships with same‐ and other‐gender peers. Gender‐integrated experiences in classrooms improved school liking and supportiveness for third to fifth graders. GI has been a neglected topic in education. This study highlights its important role in variations in school success for elementary‐aged children. There is a need for educators to promote GI.